Twilight of Teacher’s Subjectivity? - Polak, Krzysztof (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The author deals with issues of the subjectivity of the teacher he treated as an idea of the past, which today is not found in the educational realities. Subjectivity, being receptive to decision-making and willingness to bear responsibility, is understood by the author as the ability of the teacher to engage in dialogue with himself. The author characterizes the main features of such a dialogue, indicating its determinants (power, market, ideological illusions, conventions and school culture). He stresses the negative impact of transformations in the field of education, among which the prevalence of the economic-political model of the educational system nullifying the subjectivity of the teacher dominates.